CFIUS part II? The US moves to restrict outbound FDI to China - Brian J. Egan; Katie Clarke (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
The Biden Administration recently released its executive order to ban certain outbound U.S. FDI to China and implement reporting requirements for other investments in China. This Perspective provides important context for the order and highlights key issues the Administration must address in its draft rulemaking.
Keywords: 330